Different Modes of Pitch Perception and Learning-Induced Neuronal Plasticity of the Human Auditory Cortex. Issue 3 (2002) - Schulte, Michael; Knief, Arne; Seither-Preisler, Annemarie; Pantev, Christo
Abstract : We designed a melody perception experiment involving eight harmonic complex tones of missing fundamental frequencies (hidden auditory object) to study the short-term neuronal plasticity of the auditory cortex. In this experiment, the fundamental frequencies of the complex tones followed the beginning of the virtual melody of the tune "Frère Jacques". The harmonics of the complex tones were chosen so that the spectral melody had an inverse contour when compared with the virtual one. Evoked magnetic fields were recorded contralaterally to the ear of stimulation from both hemispheres. After a base line measurement, the subjects were exposed repeatedly to the experimental stimuli for 1 hour a day. All subjects reported a sudden change in the perceived melody, indicating possible reorganization of the cortical processes involved in the virtual pitch formation. After this switch in perception, a second measurement was performed. Cortical sources of the evoked gamma-band activity were significantly stronger and located more medially after a switch in perception. Independent Component Analysis revealed enhanced synchronization in the gamma-band frequency range. Comparing the gamma-band activation of both hemispheres, no laterality effects were observed. The results indicate that the primary auditory cortices are involved in the process of virtual pitch perception and that their function is modifiable by laboratory manipulation.